Rational planning of a drug candidate: in silico studies, synthesis and structural elucidation (Research, Society and Development, 2020)
Technology has been essential in the drug planning process, since it allows the optimization of time and operational costs, however, even with all this technology, the search for drugs is an arduous and highly complex process. Medicinal chemistry is the area that reconciles numerous other areas during the drug development process. Faced with this, a class of molecules that has been attracting the scientific community are carbohydrates, molecules with numerous pharmacological and biological activities. Thus, the objective of this work was to outline the molecular architecture of a drug candidate, evaluate its pharmacokinetic, pharmacodynamic and toxicological properties with the aid of in silico tools, then synthesize it and elucidate its molecular architecture. After the evaluations, it was found that the candidate deserved his synthesis, done after three reaction steps, in the form of a white amorphous solid, in excellent yield (87%). In short, in silico methods pointed out that the target candidate had a low probability of presenting toxic effects, good characteristics to become a good drug, an excellent potential for oral bioavailability and a marked activity related to enzyme inhibition.